Recent high-energy marine events in the sediments of Lagoa de Óbidos and Martinhal (Portugal): recognition, age and likely causes - P. J. M. Costa; S. A. G. Leroy; J. L. Dinis; A. G. Dawson; S. Kortekaas (Natural Hazards and Earth System Sciences, 2012)
A key issue in coastal hazards research is the need to distinguish sediments deposited by past extreme storms from those of past tsunamis. This study contributes to this aim by investigating patterns of sedimentation associated with extreme coastal flood events, in particular, within the Lagoa de Óbidos (Portugal). The recent stratigraphy of this coastal lagoon was studied using a wide range of techniques including visual description, grain-size analysis, digital and x-ray photography, magnetic susceptibility and geochemical analysis. The sequence was dated by 14C, 210Pb and Optically Stimulated Luminescence. Results disclose a distinctive coarser sedimentary unit, within the top of the sequence studied, and shown in quartz sand by the enrichment of elements with marine affinity (e.g., Ca and Na) and carbonates. The unit fines upwards and inland, thins inland and presents a sharp erosive basal contact. A noticeable post-event change in the sedimentary pattern was observed. The likely agent of sedimentation is discussed here and the conceivable association with the Great Lisbon tsunami of AD 1755 is debated, while a comparison is attempted with a possibly synchronous deposit from a tsunami in Martinhal (Algarve, Portugal). The possibility of a storm origin is also discussed in the context of the storminess of the western Portuguese coast and the North Atlantic Oscillation. This study highlights certain characteristics of the sedimentology of the deposits that may have a value in the recognition of extreme marine inundation signatures elsewhere in the world.